Study of Expression of p16 and Ki-67 in Cervical Squamous Intraepithelial Lesion and Cervical Carcinoma and Its Role as a Predictive Marker in Human Papilloma Virus Infection - Chhaya Rani Shevra; Himanshu Kumar; Mayank Singh; Sudha Sharma; Hema Shobhane (CHRISMED Journal of Health and Research)
Background: Cervical cancer is the most common cancer in women worldwide, and early diagnosis of cervical malignancies is the key of treatment and an effective screening method. Histopathology and immunohistochemistry are the gold standard for diagnosing cervical lesions. The immunohistochemistry expression of p16 together with the proliferative marker Ki-67 correlates well with the degree of cervical intraepithelial lesions and malignancies. Aims and Objectives: The present study was undertaken to study and compare the expression profile of protein p16 and Ki-67 in cervical intraepithelial and malignant lesions and its correlation with human papilloma virus (HPV) infection. Settings and Design: The present study was a prospective case–control study in a tertiary referral center. Materials and Methods: We evaluated and compared the immunohistochemical expression profile of antigens p16 and Ki-67 in 60 cases of histologically diagnosed cervical intraepithelial and malignant lesions (cervical carcinoma 24 cases, highgrade squamous intraepithelial lesion 16 cases, lowgrade squamous intraepithelial lesion 10 cases, and 10 cases of chronic cervicitis as control). Results: The mean labeling index of p16 and Ki67 was higher in cervical carcinoma (8.75 ± 0.84) than high-grade intraepithelial lesions (7.43 ± 1.93) and minimum in low-grade intraepithelial lesions (2.7 ± 2.58). Similar results were seen for Ki-67. The combined detection of p16 and Ki-67 increased the specificity to 87.5% and sensitivity to 100%. Conclusion: The study concludes that p16 and Ki-67 expression can help to distinguish between premalignant and malignant cervical lesions and p16 may be used as a prognostic marker for detecting HPV in cervical neoplastic lesions.